Analysis of the Influence of E-Service Quality, E-Satisfaction and E-Trust on E-Customer Loyalty among BRImo Mobile Banking Users in Mataram City - Baiq Marlia Apriyani; Bambang Bambang (International Journal of Business and Quality Research, 2024)
The rationale behind this study is to examine the impact of e-service quality, e-satisfaction, and e-trust on BRImo mobile banking users' customer loyalty. Purposive sampling is the sampling strategy used in this quantitative study. The primary data used in this study were gathered from 100 respondents via questionnaires. This investigation implemented multiple linear regression techniques featuring SPSS 26 as the data analysis tool. The study findings suggest that e-service quality has no own impact on the e-customer loyalty of BRImo mobile banking users, whereas e-satisfaction and e-trust have a noteworthy and favorable effect on customer loyalty